INFORMATION NEEDS OF RURAL PREGNANT WOMEN IN GUNTUR DISTRICT - S. MAMATA*, M.S.CHAITANYA KUMARI and G.MANASA (The Journal of Research ANGRAU, 2020)
The study (2018-’19) focused to identify the information needs of rural pregnant women by adoptingexploratory research design in order to address the existing knowledge gaps. A sample size of 90 ruralpregnant women from nine villages of Guntur district were selected for the study. Results indicated thatmajority of the pregnant women have expressed their information needs on antenatal registration process,laboratory tests, obstetric complications, high risk pregnancy, nutrition during pregnancy, etc. Awarenessabout various Govt. schemes and programmes was appreciable among the pregnant women as great majority(87.77%) of the respondents availed them. Information sources for the pregnant women were mainly parents(91.11%) which ranked first, followed by health department (88.88%) which ranked second, and Department ofWomen Development and Child Welfare (86.66%) which ranked third.